BAURAN PEAMSARAN ONLINE DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN DI KABUPATEN MAMUJU - Muchtar, Muchtar; Halim, Agus (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2020)
Increased internet penetration in Indonesia has led to a shift in marketing technology. This makes online sales practices that have many advantages for both companies and consumers a lot to do. Online sales cover the whole process from marketing, selling, shipping, service, and payment to consumers. However, the marketing mix through the internet changes the focus from previously only focusing on the seller's view to a more interactive situation involving consumers, making it easier for consumers to make decisions. The purpose of this study was to determine the effect of online marketing mix on consumer purchasing decisions in Mamuju Regency. The population in this study are consumers who make online purchases in Mamuju Regency whose numbers are unknown or categorized as infinity. To calculate the number of samples, this study uses the Stanley et al. (1997) because population size is unknown or infinite with a certain level of significance (α). The results of this study indicate that the indicator of the marketing mix does not have a meaningful meaning for the purchasing decision of a consumer to make online purchases. Consumer perceptions that make purchases online show that the products offered online lack variety, the quality is still low, the design and packaging are not attractive and well known, the price is less competitive and affordable, the price is not in accordance with the quality and benefits, the vendor does not have a place of existence that is clear and reliable, product catalogs and prices that are less complete and less updated, website design lacks information, lack of discounts offered, less interactive marketing systems, ordering processes and complaints are relatively easy.